2016
DOI: 10.1080/01480545.2016.1190739
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological assessment of Diplazium esculentum on the reproductive functions of male Swiss albino mouse

Abstract: These results suggest that the intake of D. esculentum, even after cooking, may induce infertility by altering the male reproductive function, and therefore, should be evaluated further as a potential antifertility agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The toxicological impact of D. esculentum on male reproductive functions of Swiss albino mice has been reported [105]. A total of 120 male Swiss albino mice of 6-8 weeks of age were fed orally with 80, 160, and 320 mg/kg b.w.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…The toxicological impact of D. esculentum on male reproductive functions of Swiss albino mice has been reported [105]. A total of 120 male Swiss albino mice of 6-8 weeks of age were fed orally with 80, 160, and 320 mg/kg b.w.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…The sub-chronic and chronic treatments at the dose of 320 mg/kg body of D. esculentum have been reported to cause 100% fertility losses. Similarly, 100% losses of fecundity were observed in mice that were treated with 160 and 320 mg/kg bw of BDE for 180 days (Roy & Chaudhuri, 2017).…”
Section: Effect Of D Esculentum On the Reproductive Functionsmentioning
confidence: 91%
“…Significant decreases in the glycogen-, protein-, sialic acid-, and citric acid contents have also been observed in D. esculentum fed mice. Moreover, it was proposed that significant decrease in the prostatic citric acid level along with the decreased acid phosphatase level in testis might alter the testosterone level in D. esculentum treated mice (Roy & Chaudhuri, 2017). D. esculentum caused various structural abnormalities in testis as indicated by the histological examinations.…”
Section: Effect Of D Esculentum On the Reproductive Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaves used as vegetables; dried rhizomes are used as an insecticide, decoction of this plant is used in the treatment of cough and sometimes as a tonic (Chawala et al 2015) providing the basic needs, this fern have got considerable anti-inflammatory and antihepatoprotective activities (Nair et al 2015) and also significant cytotoxic, anti-microbial, antioxidant properties (Akter et al 2014). However, a study revealed, even after cooking, this fern may induce infertility to the male reproductive system (Roy and Choudhuri, 2015). Another study reported that daily consumption of the fern was found to elevate the risk of esophageal cancer (Somvanshi et al 2006).…”
Section: Ethanobotanical Usesmentioning
confidence: 99%